In Silico-Predicted Cytokeratin Fragment 21-1 (Cyfra 21-1) Immunogenic Epitopes for The Early Detection of Nasopharyngeal Carcinoma - Depamede, Brian Umbu Rezi; Alisjahbana, Bachti; Depamede, Sulaiman Ngongu; Hafidhoh, Sanny; Nururrohmah, Siti; Tryawan, Ilham Ngongu; Yusuf, Muhammad (Departemen Kimia, 2024)
Nasopharyngeal Carcinoma, an aggressive cancer in the head and neck region is mostly diagnosed at an advanced stage and thus has a poor prognosis. Cytokeratin Fragment 21-1 (CYFRA 21-1) is one of the oncomarkers discovered in saliva. For developing a diagnostic kit, CYFRA 21-1 antibodies and immunogens are needed. Natural CYFRA 21-1 immunogen is difficult to obtain, so it must be made in-silico using bioinformatics. We aim to predict CYFRA 21-1 immunogenic epitope to produce antibodies polyclonal against CYFRA 21-1, which can be used to develop NPC diagnostics. The immunogenic epitopes were predicted and chosen based on antigenicity, surface accessibility, and hydrophilicity, then characteristic was analyzed and evaluated. The epitope candidates were compared with other saliva protein biomarkers to find if there were cross-reactions. CYFRA 21-1 consists of 57 amino acids, where two immunogenic epitopes (C3 and D2) were chosen. The Ramachandran Plot of both epitopes shows that 100% of the amino acids were in the favoured area. Epitopes C3 and D2 have no cross-reaction with other protein biomarkers. The predicted immunogenic epitopes have the potential as antigen to produce antibodies for developing saliva-based immunodiagnostics to early diagnose NPC patients.